(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Artificial intelligence (AI) is a modern technology that plays an unchanging and important role in the educational process. It helps to develop the learning process of the students in an effective and customized way. Artificial intelligence is bringing about a number of positive changes in the field of education, such as optimizing teaching and learning methods, offering personalized learning and enabling data-driven decision making.